Electromechanical properties of 0-3 vegetable based polyurethane and lead zirconate titanate composite. - Sakamoto, W. K.; Das-Gupta, D. K. (Inst Electrical Engineers Inspec Inc, 2000)
Composite made of Lead Zirconate Titranate (PZT) ceramic powder and castor oil based polyurethane (PU) were prepared in the thin film form with 0-3 connectivity by spin coating. The composite films were obtained in the thickness range of 100 mum to 300 mum using 33-vol.% of ceramic. The samples mechanical resistance. The material was characterised by dielectric spectroscopy, thermally stimulated discharge current (TSDC), hysteresis measurements and laser-intensity-modulation method (LIMM). The pyroelectric coefficient at 343 K was 7x10(-5) C.m(-2) K-1 for the sample poled with 10 MV/m at 373 K for Ih. The results show that this new composite can be used as suitable piezo and pyroelectric sensors.